The Role of Financial Behavior in Mediating Financial Literacy, Financial Attitudes, Business Performance and Business Sustainability in MSMEs in Jayapura City - Sesa, Pascalina Van Sweet; Wonar, Klara; Allolayuk, Theo (AIBPM Publisher, 2024)
Examining how financial conduct affects financial behavior, financial attitudes, company performance, and sustainability of MSMEs in Jayapura City is the aim of this study. It is anticipated that the analysis would serve as a helpful guide for next studies. This study is quantitative in nature and tests hypotheses using a descriptive methodology. The way that data is gathered is through distributing questionnaires. One tool for data analysis methods is WarpPLS analysis.The findings showed that business performance and financial literacy had a favorable and substantial influence on financial behavior. On the other hand, financial behavior is not significantly and favorably impacted by financial attitudes. Financial management practices and financial literacy have a big impact on a company's capacity to survive. Financial attitudes and business performance have little bearing on a company's capacity to survive. As a mediating variable between financial literacy and company performance, financial management behavior has a big impact on the sustainability of businesses. Regarding financial attitudes toward business sustainability, there is no discernible effect of financial management conduct as a mediating variable.